ONLINE AND OFFLINE EDUCATION: INNOVATIVE APPROACHES IN MODERN LEARNING (British Journal of Global Ecology and Sustainable Development, 2025)
This article explores the evolution of education in the digital age, emphasizing the integration of online and offline learning models. It discusses the advantages, challenges, and innovations associated with both systems, focusing on how their combination—known as blended learning—enhances student engagement, motivation, and critical thinking. The study argues that the future of education lies in flexibility, collaboration, and the effective use of modern technologies that support independent and interactive learning.